Evaluation of ethnic disparities in detection of depression and anxiety in primary care during the maternal period: Combined analysis of routine and cohort data. (May 2016) - Prady, Stephanie L.; Pickett, Kate E.; Petherick, Emily S.; Gilbody, Simon; Croudace, Tim; Mason, Dan; Sheldon, Trevor A.; Wright, John
Abstract : Background: There are limited data on detection disparities of common mental disorders in minority ethnic women. Aims: Describe the natural history of common mental disorders in primary care in the maternal period, characterise women with, and explore ethnic disparities in, detected and potentially missed common mental disorders. Method: Secondary analyses of linked birth cohort and primary care data involving 8991 (39.4% White British) women in Bradford. Common mental disorders were characterised through indications in the electronic medical record. Potentially missed common mental disorders were defined as an elevated General Health Questionnaire (GHQ-28) score during pregnancy with no corresponding common mental disorder markers in the medical record. Results: Estimated prevalence of pre-birth common mental disorders was 9.5%, rising to 14.0% 3 years postnatally. Up to half of cases were potentially missed. Compared with White British women, minority ethnic women were twice as likely to have potentially missed common mental disorders and half as likely to have a marker of screening for common mental disorders. Conclusions: Common mental disorder detection disparities exist for minority ethnic women in the maternal period.